Impactos causados da aplicação de água residuária de suinocultura em latossolo cultivado com soja - Maggi, Cacea Furlan (2009)
The objective of this work was to evaluation the possible impacts of soil and drainage of leaching from lysimeters with different rates of swine wastewater application in soil with soybean and to assess the productivity of it. The experiment was conducted in the UNIOESTE Experimental Center of Agricultural Engineering, the soil was classified as Clayey Typic Haplusdox. In the twenty-four had drainage lysimeters it was planted to soybean, cultivar CD 214. Seven days before planting were applied four rates of swine wastewater (ARS) (0, 100, 200 and 300 m³ ha-¹) in a single application, combined with two fertilizer at sowing (with addition and without addition of fertilizer recommended at sowing) and three replicates per treatment. There were three samples of soil in each experimental plot, the first at 40 days after sowing (DAS), the second and third of 72 to the end of the cycle (117 DAS). Evaluated the pH, calcium, magnesium, potassium, phosphorus, organic carbon, total nitrogen, cation exchange capacity and sum of bases. It were collected on the same dates of the soil samples from the lysimeters leaching material in which it was determined the pH, calcium, magnesium, potassium, phosphorus, total nitrogen, nitrate and electrical conductivity. The productivity, number of pods per plant, number of seeds per plant and number of seeds per pod was available. The experimental was blocks in factorial (4x2) for the components of the production of soybean. For the experimental blocks in factorial (4x2) and subplots in time for the chemical analysis of soil and leaching. Based on the results the values of pH and Ca in soil and leaching were not influenced by the application of ARS and fertilization. The level of K, P and N in soil increased linearly with the increased rates of ARS. The levels of K, P and nitrate in the leaching were higher for higher rates of ARS. The values of pH, Ca and nitrate in the leaching decreased over the collections. The yield was not influenced by the application of ARS nor by fertilization.